Five Love Languages Scale Factor Analysis - Surijah, Edwin Adrianta; Kirana, Cokorda Tesya (Makara Human Behavior Studies in Asia, 2020)
This research reexamines composing factors of the Five Love Languages. Previous research has shown differing results on this topic. The Five Love Languages were measured by adapting the Five Love Languages Scale. This scale was then modified to lengthen participants’ response range and add one ancillary item. The research sample comprised of 687 undergraduate students and selected through proportionate quota sampling. Sample age ranges were between 17 and 40 years old. Exploratory factor analysis showed items were laid out accordingly with factor loading for each item ranging from 0.463 up to 0.853. EFA also exhibited love language is constructed by four components. The unique aspect found on this research was sacrificial element.